Analisis Cemaran Bakteri Coliform pada Makanan Tradisional Sotong Pangkong di Jalan Merdeka Kota Pontianak Berdasarkan Nilai Most Probably Number (MPN) - Rahmawati, Darna, Masnur Turnip (Universitas Tanjungpura, 2017)
Coliform bacteria can contaminate food and lead to intoxication causing symptoms of human digestive tract disorders. Food which is vulnerable to the contamination coliform bacteria is traditional food which is processed in a simple. One of Pontianak traditional food is sotong pangkong. The purpose of this research is to study the contamination of coliform bacteria on sotong pangkong sold on Jalan Merdeka, Pontianak. The research was conducted for three months from September to November 2016 it the Microbiology Laboratory of the Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. This research was observative and descriptive in nature,the data were tabulated by presenting table. The result showed that the sample of sotong pangkong was contaminated by coliform bacteria in which the MPN values was above the maximum limit, except for sample which had been roasted from seller IV (<3 MPN/gram). The highest contamination sample before and after roasted were gathered from seller I and seller III where the value was >1100 MPN/gram. Meanwhile the lowest contamination on the sample before-roasted sample was recorded from seller II by 11 MPN/gram. The bacteria contamination was above the limit of bacterial contamination based on BPOM No. HK.00.06.1.52.4011 Year 2009 by <3/gram.